Detecting trends and further development potential of contemporary façade design for workspaces. (4th July 2019) - Pastore, Luisa; Andersen, Marilyne
ABSTRACT: Façade design is claimed to fulfil a number of requirements in workplaces, ranging from privacy to safety and from comfort to aesthetics. For future R&D efforts in façade design, identifying the key drivers that should shape contemporary facades in office buildings is not always an easy task because of the discrepancies that can emerge between the diverse expectations from professionals and the possible conflicts that can exist in conciliating global design trends with local climate constraints. This research aims to enrich the debate on façade design developments for office buildings, by discussing the outcomes of an on-line survey distributed worldwide among professionals working in the building design sector. Outcomes of 245 responses are summarized in an interactive chart that enables to visualize the potential of some main aspects and technologies characterizing today's office building skins. The potential is shown based on the observed level of relevance among different professional profiles or climates. While energy and comfort emerged as the aspects attaining global and interdisciplinary consensus, the features that entailed psychological or emotional reactions attracted the most diverse evaluations. Despite not being fully exhaustive, the observations arising from this study can help with identifying possible research and developments gaps in the field.